2008
DOI: 10.3171/foc/2008/24/6/e3
|View full text |Cite
|
Sign up to set email alerts
|

Management of brain abscess: an overview

Abstract: ✓ Recent advances in neuroimaging have resulted in a marked decrease in morbidity and death due to brain abscesses. The advent of computed tomography–guided stereotaxy has reduced morbidity in patients with deep-seated abscesses. Empirical therapy is best avoided in the present era, particularly given the availability of stereotactic techniques for aspiration and confirmation of diagnosis. Despite these advances, management of abscesses in patients with cyanotic heart disease and in immunosuppressed pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
138
0
7

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(145 citation statements)
references
References 51 publications
0
138
0
7
Order By: Relevance
“…Therefore surgical intervention is essential once the capsule is formed. [17][18][19][20] Hence brain abscess following CSOM can be effectively managed if evolution pattern is known, as the treatment is mainly based on the stage of abscess formation.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore surgical intervention is essential once the capsule is formed. [17][18][19][20] Hence brain abscess following CSOM can be effectively managed if evolution pattern is known, as the treatment is mainly based on the stage of abscess formation.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Benedetti et al and Murray et al reported gemella brain abscess after 3 weeks of antibiotic therapy for gemella meningitis. In anticipation of complete eradication of the gemella, it is needs to be emphasized that whatever regimen is used, it should be continued for a period not less than 6 weeks, (12) or continued till the C reactive protein falls to normal levels (6).…”
Section: Discussionmentioning
confidence: 99%
“…As well comprehended, CT guided stereotactic aspiration is the modality of choice with deep seated and multiple abscesses (9,(11)(12). Messori et al (11) reports the use of stereotactic aspiration in a patient with a fronto parietal abscess, who then developed a cortical lesion at the site of the needle procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Management of a usual brain abscess includes either aspiration by various techniques and 6-8 weeks of antibiotics. In patients unresponsive to antibiotics, large abscesses causing significant mass effect and neurological deficits, and in multi-loculated abscesses craniotomy and excision of abscesses is indicated 3 . A deficiency of vitamin K-dependent clotting factors, decreased and defective platelets, and accelerated fibrinolysis results in abnormal hemostasis with frequent and increased bleeding.…”
Section: Discussionmentioning
confidence: 99%